KEEFEKTIFAN MAL PELAYANAN PUBLIK PADA PENYELENGGARAAN PELAYANAN ADMINISTRASI KEPENDUDUKAN DI KABUPATEN SUMEDANG - NABABAN, WIRANATA; Tahir, Irwan; Wasistiono, Sadu (Institut Pemerintahan Dalam Negeri, 2023)
Abstract Public Service Mall (MPP) is a place where activities or public service delivery activities take place for goods, services and/or administrative services to provide services that are fast, easy, affordable, safe and comfortable. Public Service Mall (MPP) is a bridge that connects and brings the government closer to its people. The purpose of this study is to determine the effectiveness of public service malls in the implementation of population administration services in Sumedang district. The theory used in this study is the theory according to Gibson (1996) about organizational effectiveness with 5 indicators namely Production, Quality, Efficiency, Flexibility, Satisfaction and Development. This research method is descriptive with a qualitative approach. The informants were determined in three ways, namely purposive sampling, snowball sampling and accidental sampling. The data collection techniques used were interviews, observation, documentation and data triangulation. Data analysis techniques were carried out by Data Reduction, Data Presentation and Data Verification. The results of the study show that the presence of Public Service Malls in the administration of population administration services is generally effective, although there are several elements that influence the achievement of effectiveness. This can be seen from the dimensions used in this study. The development aspect has not been carried out in a sustainable manner in terms of budget support and program activities. Keywords: Effectiveness, Public Service Mall, Population Service